A STUDY OF STUDENTS’ AND TEACHERS’ PERCEPTIONS TOWARDS USING LOCAL FOLK STORIES FOR IMPROVING ENGLISH READING SKILLS AT KUNSHAN DEVELOPMENT ZONE SENIOR HIGH SCHOOL, JIANGSU PROVINCE, CHINA - WANG, YU; Eamoraphan, Suwattana (Scholar: Human Sciences, 2022)
This study was to determine the students’ and teachers’ perceptions on using local folk stories for improving English reading skills at Kunshan Development Zone Senior High School, Jiangsu Province, China. There were two research objectives in this study: (1) to identify the students’ perceptions on using local folk stories for improving English reading skills at Kunshan Development Zone Senior High School, Jiangsu Province, China. (2) to identify the teachers’ perceptions on using local folk stories for improving English reading skills at Kunshan Development Zone Senior High School, Jiangsu Province, China. There were 244 Grade 11 students and 10 English teachers participated in this study. In order to carry out the research, the researcher used the explanatory mixed methods collect the data. The research instruments used were 5-point Likert scale questionnaire for students and structured interview for teachers.[1]The findings indicated that (1) the Grade 11 students studied at Kunshan Development Zone Senior High School have positive attitudes on using local folk stories for improving English reading skills. Since the total mean score of students’ perceptions on using local folk stories for improving English reading skills was interpreted as high on the interpretation scale. (2) the teachers who taught Grade 11 at target school believed the application of folk stories in English reading teaching was useful for students to improve their reading skills, and they were prone to use folk stories in their future teaching English class.